Effect of gestational weight gain on pregnancy outcomes in underweight pregnant women - Suttanaratt Apiwantana (Thai Journal of Obstetrics and Gynaecology, 2013)
Objective:To determine a relationship between inadequate gestational weight gain and adverse pregnancy outcomes among Thai gravidas with underweight. Methods: A retrospective cohort study was conducted in 306 underweight pregnant women who attended our antenatal clinic between December 2009 and August 2012. The study subjects (women who gained less than 12 kg throughout pregnancy) were matched 1:1 with the control subjects (women who gained ≥12 kg) by age group and parity. Adverse pregnancy outcomes including low birth weight (LBW), small-for-gestational age (SGA), birth asphyxia, and neonatal intensive care unit (NICU) admission were compared between the two groups.Results: Complete data of 145 study subjects and 145 controls were analyzed. The study group had significantly lower mean neonatal birth weight than the control group: 2,939.0±338.1 grams vs. 3,037.2±336.9 grams; p=0.014. By univariable and multivariable analyses, women in the study group were not at increased risk of LBW, SGA, birth asphyxia, and NICU admission compared to control subject. However, when different thresholds for inadequate weight gain were applied, we found that gestational weight gain less than 8 kg was significantly associated with LBW, but not SGA, birth asphyxia, and NICU admission, in underweight women. The adjusted OR was 4.5 (95% confidence interval, 1.4-14.6; p=0.012). Conclusion: There was no significant relationship between inadequate gestational weight gain (<12 kg) and adverse pregnancy outcomes among Thai gravidas with underweight. However, women who gained less than 8 kg were at significantly increased risk of delivering a LBW infant.